Assessment of tubal patency through sono-hysterosalpingography using B-mode and colour Doppler: a comparative study - Gupta, Bhavini; Pasoria, Sanjay; Manmohan, Madan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Tubal factors constitute a major proportion of infertility causes, and include disorders affecting one or more components of the fallopian tube. Demonstration of tubal patency using imaging modalities can help lower the rate of invasive diagnosis and management. Hysterosalpingography provides optimal delineation of fallopian tube anatomy, allowing detection of tubal patency, tubal occlusion, and peri-tubal disease. Sonosalpingography with saline infusion was started as an alternative because of its added benefits of structural and morphological abnormality detection. Methods: Patients referred for primary and secondary infertility were assessed on B-mode ultrasound trans-abdominally, followed by cervical catheterization and trans-vaginal ultrasound. Sterile saline fluid was pushed through the cervix, to use as a contrast medium, and its movement was assessed on B-mode and as a colour Doppler artefact. Results: B-mode, colour Doppler and presence of free-fluid in pouch of Douglas showed presence of tubal patency in 59.6%, 82.7% and 78.8% cases respectively and presence of bilateral and unilateral tubal block in 60.4%, 17.3% and 21.2% respectively. Diagnostic accuracy of B-mode and colour Doppler is 84.6% and 95.2% respectively. Conclusions: Sonosalpingography can be used to pin-point the exact location of the tubal block, due to its real-time imaging benefits. Normal saline infusion can be used effectively. Colour Doppler provides higher sensitivity for evaluation of tubal patency and has higher specificity for tubal block. Used in combination, they improve diagnostic accuracy and efficacy of sonosalpingography.